2018
DOI: 10.1038/s41423-018-0022-2
|View full text |Cite|
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor signaling promotes ORMDL3-dependent generation of sphingosine-1-phosphate by inhibiting sphingosine-1-phosphate lyase

Abstract: Aryl hydrocarbon receptor (AhR), a cellular chemical sensor, controls cellular homeostasis, and sphingosine-1-phosphate (S1P), a bioactive intermediate of sphingolipid metabolism, is believed to have a role in immunity and inflammation, but their potential crosstalk is currently unknown. We aimed to determine whether there is a functional linkage between AhR signaling and sphingolipid metabolism. We showed that AhR ligands, including an environmental polycyclic aromatic hydrocarbon (PAH), induced S1P generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
(66 reference statements)
1
27
0
Order By: Relevance
“…Consistent with our previous reports , an AhR ligand, FICZ, was shown to enhance the levels of mast cell degranulation and cytokine release following the cross linkage of Ag (OVA) and OVA‐specific IgE Abs (Fig ). To examine whether metformin was able to regulate IgE‐mediated mast cell activation and AhR ligand's impact, varying doses (1 μM–1 mM) of metformin was initially evaluated for its effect on mast cell degranulation.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with our previous reports , an AhR ligand, FICZ, was shown to enhance the levels of mast cell degranulation and cytokine release following the cross linkage of Ag (OVA) and OVA‐specific IgE Abs (Fig ). To examine whether metformin was able to regulate IgE‐mediated mast cell activation and AhR ligand's impact, varying doses (1 μM–1 mM) of metformin was initially evaluated for its effect on mast cell degranulation.…”
Section: Resultssupporting
confidence: 91%
“…Further, exposure of mast cells to FICZ increased the intracellular ROS levels, which were reversed following the addition of an antioxidant, N‐Acetyl‐Cysteine (NAC), and metformin (Fig A). Our previous report has shown that AhR negatively regulated the enzymatic activity of sphingolipid‐1‐phosphate lyase (S1PL) through increased ROS and oxidation of S1PL ; thus, we tested whether metformin could block the negative regulation of AhR on the enzymatic activity of S1PL through the inhibition of ROS production. As S1PL‐specific Abs were not available for immunoprecipitation assay and the low transfection efficiency of BMMCs, we employed an enforced overexpression of flag‐tagged‐S1PL in a human mast cell line, HMC‐1, instead.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations